Evaluation of physical capacities of strength and speed of different competition level young football players - Gissis, I. (Journal of Physical Education and Sport, 2012)
The purpose of this study was to assess the physical abilities of strength and speed of young soccer players of different competition level. Forty-eight (n=48) soccer players were divided into three groups according to competition level: Elite class young football players of higher division (n=16), who competed in a higher division championship, middle class young football players of middle division (n=16), who competed in a middle class championship and lower class young football players of lower division (n=16), who competed in a football academy. All groups were evaluated for maximal isometric force, explosive force at 100 msec, peak force relative to body mass, rate of force development, squat and drop jump heights of 20 cm, drop jump heights of 30 cm, drop jump heights of 40 cm, pedaling rate and 10 m sprint time. Elite class young football players presented significantly (p<0.05) higher maximal isometric force, vertical jump height, pedaling rate, and lower 10 m sprint time in comparison with the middle class young football players and lower categories. Also we observed statistically significant differences in selected variables between middle class young football players and lower categories. These strength and speed measures can be used for strength and speed diagnosis, and for designing and evaluating training programs.